The food-energy-water-land-biodiversity (FEWLB) nexus through the lens of the local level : an agricultural case study - Hulley, Sarah May (Department of Environmental and Geographical Science, 2016)
There is a recognised need to turn the abstract concept of resilience thinking into practical action for resource management. This is often difficult as resource management is complex and multifaceted. Nexus thinking attempts to address this by promoting a framework that integrates and coordinates resource management across many different but interlinked resource pillars and sectors. This research focuses on the local level implementation of the food, energy, water, land and biodiversity (FEWLB) nexus framework, and assesses farmers' understanding and implementation of nexus thinking in relation to the support of the Bergrivier Municipality. Agriculturalists (farmers) have been described as significant custodians of natural resources, as they sit in a key position when it comes to implementing and practising sustainable development. There has been little research into the relationship between farmers and local municipalities, or into the role that local government can play in supporting holistic resource management through agriculture. While there are many different actors contributing towards resource management, this research focuses on the agricultural sector within the municipality. Qualitative research methods, including semi-structured interviews, participant observation and surveys, were used to undertake a case study of the agricultural sector within the Bergrivier Municipality. In a context where local government struggles to find its role in supporting socio-ecological resilience, the FEWLB nexus framework offers an opportunity to implement effective planning and policies that could enable more efficient resource use.